Femorotibial bypass: the learning curve. - Wyatt, M. G. (Royal College of Surgeons of England, 1995)
Femorotibial bypass is still infrequently performed in many district hospitals, because it is time consuming and the risk of failure is high, especially during the learning curve. This article reviews the results of a single consultant surgeon and his team after starting femorotibial bypass de novo in a district general hospital. During the period 1987 to 1992, 85 femorotibial grafts were performed in 76 patients for ulceration and gangrene (57), rest pain (19) and severe claudication (9). Sixty-six were autogenous vein, 15 were PTFE with distal vein cuff, two were composites and two were umbilical vein. Overall, 22 grafts (26%) failed within the first 30 days (two were salvaged) and 21 amputations were required (five despite patent grafts). There were three early deaths (mortality 3.9%). At the end of 1993, 39 limbs had been amputated and 24 patients had died (eight with amputations). Twenty-three (44% of survivors) were alive with patent grafts. These disappointing early results were due to an initial technical learning curve, after which increased confidence may have led to reconstructing some patients with inadequate distal arteries. A more selective approach is now used. Limb salvage can be achieved in a worthwhile proportion of these patients and 3-year primary patency rates are similar to those of teaching hospitals in this country.